Business study mission to Argentina, Chile & Peru : the nature of foreign investment in Argentina, Chile and Peru. - Lim, Jit Yin. (2010)
Just as Latin America shakes off the last vestiges of the Mexican "Tequila hangover" in 1995, it now faces the economic fallout from an Asian crisis, potential collapse of the Russian economy and the devaluation of the Brazilian currency, the real. The International Monetary Fund (IMF) and overnments worldwide fear that a full blown crisis in Brazil would drag all Latin America into recession, hurting U.S. exports to the region and slowing economic growth (Reuters, 3 March 1999). Latin America is a region less known to most Asian economies. Remembered more for its four-digit inflation rates, political instabilities and frequent policy changes, the region was just beginning to receive foreign direct investment (FDI) from non-traditional sources in Asia when the Asian crisis hit. But with few cultural, historical or social links, accentuated by geographical distance, investment activities between Asian and Latin American countries were limited. However, Latin American countries are liberalising FDI legislation and controls in an attempt to develop local industries.